Histopathological Spectrum of Nephrectomy Specimens - R, Madhu Kumar; P, Meghana; Vasudev, Vidya; M, Bharathi (Annals of Pathology and Laboratory Medicine, 2019)
Background: Kidneys are the vital organs of the body which are having multiple functions. The benign or malignant diseases of the kidney result in total organ removal. Renal tumors comprise a wide spectrum of neoplastic lesions with patterns that are distinct for children and adults. In India management of chronic kidney diseases is a great challenge as the dialysis and kidney transplantations are expensive. Objectives: To study histopathological features of various nephrectomy specimens and to determine the age and sex distribution in various renal lesions. Materials and Methods: The study is done in Mysore medical college and research institute. Total 50 nephrectomy cases were studied in a period of 2 years from 2015 to 2017. Result: Total of 50 nephrectomy cases were studied out of which 27 were male and 23 were female with ratio of 1.17:1. The non-neoplastic and neoplastic cases were 36 and 14 respectively, with ratio of 1.44:1. In non-neoplastic chronic pyelonephritis is most common 21 cases (58.3%), followed by hydronephrosis - 5 (13.9%) cases, tuberculous pyelonephritis - 3 cases (8.3%), Xanthogranulomatous Pyelonephritis - 2 cases (5.6%). Simple renal cyst, Polycystic kidney disease, End stage kidney disease, RTA and Ischemic atrophy - 1 case each. In neoplastic RCC is the most common - 10 cases, followed by SCC and Angiomyolipoma - 2 cases each. Most of the patients presented in age group of 4th to 5th decade and histologically RCC-clear cell type was the most common subtype. Conclusion: Chronic pyelonephritis is most common non neoplastic lesion and RCC is the most common neoplastic lesion in which clear cell type is most common subtype.